2021
DOI: 10.3390/ijerph18136930
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment on Ethanol-Blended Gasoline/Diesel Fuels on Cancer Risk and Mortality

Abstract: Although cancer is traditionally considered a genetic disease, the epigenetic abnormalities, including DNA hypermethylation, histone deacetylation, and/or microRNA dysregulation, have been demonstrated as a hallmark of cancer. Compared with gene mutations, aberrant epigenetic changes occur more frequently, and cellular epigenome is more susceptible to change by environmental factors. Excess cancer risks are positively associated with exposure to occupational and environmental chemical carcinogens, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 280 publications
0
5
0
Order By: Relevance
“…It is considered one of the best ways of reducing tailpipe emissions [69]. It is more volatile than gasoline and therefore evaporates more easily.…”
Section: Ethanol (Ethyl Alcohol)mentioning
confidence: 99%
“…It is considered one of the best ways of reducing tailpipe emissions [69]. It is more volatile than gasoline and therefore evaporates more easily.…”
Section: Ethanol (Ethyl Alcohol)mentioning
confidence: 99%
“…Chia mitigated the stimulatory effect of xylene on proliferation but not on other parameters in both bovine and porcine ovarian cells. It could be proposed that chia could be potentially useful as a protector against the stimulatory action of xylene on ovarian cell proliferation that could result in cancer development (Mueller et al, 2021;Niaz et al, 2015). The potential of chia as a natural protector against the harmful action of xylene and anticancer drugs could be promising from a medicinal viewpoint.…”
Section: Does Chia Mitigate Xylene Action On Ovarian Cell Functions?mentioning
confidence: 99%
“…The increased proliferation of xylene-treated cells could be due to increased IGF-I release. These events could explain the ability of xylene to induce malignant transformation (Mueller et al, 2021;Niaz et al, 2015), which can be due to hypertrophied IGF-I-induced cell proliferation (Chen et al, 2020). Furthermore, the ability of xylene to jeopardize fertility and gravidity (Hood & Ottley, 1985;Niaz et al, 2015;Ungváry et al, 1981) can be explained by the inhibited release of progesterone, which is a key hormone that maintains the ovarian cycle and gravidity (Sirotkin, 2014).…”
Section: Does Xylene Affect Ovarian Cell Functions?mentioning
confidence: 99%
“…Among them, toluene usually accounts for the highest proportion [8]. Relevant studies have shown that toluene has a significant contribution to the risk of carcinogenesis [9]. In the atmosphere, the concentration of toluene is usually low, generally on the order of 10ppb, but it can be as high as 10ppm in heavily polluted areas [10].…”
Section: Introductionmentioning
confidence: 99%